2021
DOI: 10.1590/1980-5373-mr-2020-0335
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ti on Microstructure, Mechanical Properties and Corrosion Behavior of a Nickel-Aluminum Bronze Alloy

Abstract: Nickel-aluminum bronze (NAB) alloys are suitable, in cast condition, to be used in marine propellers due to its excellent behavior avoiding erosion and cavitation as well as corrosion. A complex microstructure, intrinsic to this copper base system, is the result of a well-controlled chemical composition. There are few works related to the effect of adding small quantities of specific chemical elements on NAB alloys properties. The aim of this paper is to study the effect of Ti on the microstructure, mechanical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…109 In addition to modifying the chemical composition of the alloy surface for better corrosion performance, the addition of alloying elements to the bulk material can also influence its corrosion behavior. For example, while the addition of a small quantity of Ti was found to have no significant effect on the corrosion response of NAB alloy, 111 higher content of Ti up to 0.478 wt% 112 as well as Cr addition 110 contributed to better protection performance of the oxide film formed on the alloy.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…109 In addition to modifying the chemical composition of the alloy surface for better corrosion performance, the addition of alloying elements to the bulk material can also influence its corrosion behavior. For example, while the addition of a small quantity of Ti was found to have no significant effect on the corrosion response of NAB alloy, 111 higher content of Ti up to 0.478 wt% 112 as well as Cr addition 110 contributed to better protection performance of the oxide film formed on the alloy.…”
Section: Discussionmentioning
confidence: 95%
“…These findings were supported by various corrosion tests, as well as surface analysis using X-ray photoelectron spectroscopy (XPS). 109 In addition to Ni 108 and Cr, 109 other alloying elements [110][111][112] have been studied for their effect on the corrosion resistance of NAB. For Cr addition, it has been reported that a higher amount of Cr can improve the electrochemical corrosion resistance, although these findings were not corroborated using surface analyses and other experiments.…”
Section: Uniform (General) Corrosionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through rigorous testing, we aim to establish a clear relationship between the silicon variation and the alloy tensile strength, ductility and hardness with respect to the deformation percentage. Corrosion resistance is another crucial property for materials used in marine environments, where the presence of saltwater can lead to rapid degradation of materials (Poorjary et al, 2023;Rivero et al, 2021). The role of silicon in improving the corrosion resistance characterization of NAB alloy is a focus of ongoing research.…”
Section: Introductionmentioning
confidence: 99%
“…This refinement is particularly beneficial in reducing crack propagation along coarser K I and K II phase boundaries. Furthermore, the introduction of titanium as a dopant has shown promise, leading to improved mechanical characteristics and the formation of finer grains in NAB alloys 9 . Notably, the addition of tin to brass has resulted in the emergence of a new phase, thereby enhancing the alloy's hardness through microstructural alterations 10 .…”
Section: Introductionmentioning
confidence: 99%